Chroma consistency and luminous efficacy for a WLED using remote phosphor configuration with a tri-layer design - Phuc Dang Huu; Phan Xuan Le (Universitas Ahmad Dahlan, 2022)
The light quality of white-light-emitting diodes (WLEDs), an essential element for the improvement of WLEDs performance, can now be estimated by the angular color uniformity (ACU). In this study, a single micro-patterned layer is used to compare the variations between the traditional remote phosphor (RP) layer and the remote phosphor layer (single remote micro-patterned phosphor film (RMPP) layer). Furthermore, we investigate the application of a novel triple remote phosphor layer to improve the ACU in RP down-light lamps. Besides, the optical efficiency of the layers as well as the distribution for the angular correlated color temperature (ACCT) were also measured experimentally. According to the findings, the dual-RMPP-layer structure can achieve better chromatic uniformity with just 441 K of correlated color temperature (CCT) variance. Meanwhile, the single RMPP layer shows an ACCT deviation of 556 K and RP film structure of 1390 K. The simulation incorporating e finite-difference time-domain (FDTD) as well as the approach of ray-tracing ensures an increase in ACU. Furthermore, compare to the traditional RP layer, the single and dual RMPP layers configuration result in respective luminous efficiency ameliorations of 6.68% and 4.69%. The scattering principle and combining influence from the micro-molded layer may explain the enhancement in ACU as well as lumen.